Peningkatan Pengetahuan dan Perilaku Personal Hygiene Anak di Panti Asuhan Baiturrahmah Kampar - Elva Susanty; Yusdiana Yusdiana (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
Personal hygiene is an effort to maintain personal hygiene and health. Knowledge about personal hygiene needs to be known by children from an early age so that children avoid diseases such as worms, dental caries, and others. Increased knowledge will improve personal hygiene behavior in a better behavior. This community service activity aimed to increase children's knowledge about personal hygiene, improve personal hygiene behavior, and to find out the description of dental and oral health in children at the Baiturrahmah Orphanage, Kampar Regency. The method used in this community service activity was education, dental and oral health check up. This community service activities began with pretest, education, post test, and dental and oral health check up. The results of this service activity showed an increase in knowledge about personal hygiene, especially about dental and oral health, as well as hand washing WHO 6 steps by 18.01%, there were 59.26% of children suffering from dental and oral diseases such as superficial caries, chronic pulpitis, pulp gangrene, pulp polyps, crowding, and impacted teeth. It is necessary to carry out routine dental and oral health check up on children at the Baiturrahmah Orphanage and familiarize children with good personal hygiene behavior.